2022
DOI: 10.1038/s41598-022-11037-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo production of fluorine-18 in a chicken egg tumor model of breast cancer for proton therapy range verification

Abstract: Range verification of clinical protontherapy systems via positron-emission tomography (PET) is not a mature technology, suffering from two major issues: insufficient signal from low-energy protons in the Bragg peak area and biological washout of PET emitters. The use of contrast agents including 18O, 68Zn or 63Cu, isotopes with a high cross section for low-energy protons in nuclear reactions producing PET emitters, has been proposed to enhance the PET signal in the last millimeters of the proton path. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In preparation for radiobiology experiments (España et al 2021) at the 10 MeV proton beam (waterequivalent range of 1.2 mm) of CMAM (https://cmam.uam.es/en) Cockroft-Walton tandem electrostatic accelerator (Enguita et al 2004), we have investigated an accurate dosimetry protocol for low-energy proton beams. Radiochromic films (RCF) are a standard, widely used method of passive dosimetry (Niroomand-Rad et al 2020) presenting near tissue equivalence and very high spatial resolution (Devic et al 2016).…”
Section: Name Only a Few Examples)mentioning
confidence: 99%
“…In preparation for radiobiology experiments (España et al 2021) at the 10 MeV proton beam (waterequivalent range of 1.2 mm) of CMAM (https://cmam.uam.es/en) Cockroft-Walton tandem electrostatic accelerator (Enguita et al 2004), we have investigated an accurate dosimetry protocol for low-energy proton beams. Radiochromic films (RCF) are a standard, widely used method of passive dosimetry (Niroomand-Rad et al 2020) presenting near tissue equivalence and very high spatial resolution (Devic et al 2016).…”
Section: Name Only a Few Examples)mentioning
confidence: 99%
“…However, these isotopes are produced by nuclear interactions along the proton beam path with a relatively high energy production threshold, implying that they will not be formed near the Bragg peak [11]. As a result, an alternative methodology has been proposed that consists of using contrast agents [12][13][14][15][16][17] and external media that facilitate the production of detectable activity closer to the Bragg peak. One of the proposed materials is zinc, which leads to the production of isotopes such as 66 Ga and 68 Ga via proton-induced reactions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Based on own previous studies and data from other groups, the model appears suitable for efficient initial in vivo screening of the biodistribution of novel radiolabeled compounds prior to the evaluation in small animals [ 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. However, testing for target specificity of a radiolabeled tracer by blocking studies has not yet been demonstrated in the CAM model.…”
Section: Introductionmentioning
confidence: 99%